Training For Medical Records Officers As Preparation To Become Clinical Instructure (Ci) In Health Service Facilities - Nurhasanah Nasution (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Hospital human resources have authority in carrying out medical record and noting health information is medical record officer. On their duties, medical record officer has responsibility to serve patient based on basic management of medical record and health information. This responsibility is included their main duty had given as authority become a clinical instructure (CI) and also as student assistant in their field training activities. CI itself has fuction to plan, manage and evaluate all of thing that related to clinical training. Offenly, CI face many problems while nurturing traine’s student because of less confident and unclear appointments or duties has given by the educational institution through CI. According to the preliminary study had done at Aisyiyah Kota Padang Hospital shown that medical recorder officer are not trained yet related to role as CI. This problem has attracted the writer to held the CI training at Aisyiyah Hospital. Writer has assumed that CI supporting the hospital accreditation status. This activity was held from 6 – 7 October 2022 at Aisyiyah Hospital and has trained 14 participants consist of college team, hospital director, and staffs (doctor’s, nurses and medical record officer). In Coclusion, partisipants very antusiastic in training had proven by high score at final examination. Keywords : Clinical Instructure, Medical record, Hospitall, Training.